Perancangan Alat Pembentuk Lembaran Mie Basah yang Ergonomis dengan Pendekatan Rekayasa Nilai - Diah Kusumawardhani; Guntarti Tatik Mulyati; Wahyu Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
To operate machines during the producing wet-noodle sheets processes involve both crews' hands and physical activities. The constructed structures for such machines which are not suitable for the operators's physical anthropometry may ultimately affect the operators' performances. Accordingly, declining in production quantities and qualities are unsurprising. Three stages are involved in designing and construction of such machines based on the above approaches. Namely identifying a set of operators' associated needs (which are gathered through questionaires), secondly is developing the ergonomics machine concept through FAST diagram and the last stage is analyzing the machines' overall expected value and performances. These design stages are performed on the main machine structure, the mixed blend basin, the milled paste container and on the handle grip to rotate the milling device. Studies indicated that machines constructed through these methods produced increamental of performance by 2.56% and value by 3.72 % respectively.